2014
DOI: 10.2337/dc13-2899
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of a Mediterranean Diet on the Need for Diabetes Drugs and Remission of Newly Diagnosed Type 2 Diabetes: Follow-up of a Randomized Trial

Abstract: OBJECTIVETo assess the long-term effects of dietary interventions on glycemic control, need for diabetes medications, and remission of type 2 diabetes. RESEARCH DESIGN AND METHODSOriginally, in a two-arm trial design, overweight, middle-aged men and women with newly diagnosed type 2 diabetes were randomized to a low-carbohydrate Mediterranean diet (LCMD; n = 108) or a low-fat diet (n = 107). After 4 years, participants who were still free of diabetes medications were further followed up until the primary end p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
150
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 160 publications
(154 citation statements)
references
References 29 publications
(20 reference statements)
2
150
1
1
Order By: Relevance
“…An extensive metaanalysis including 136,846 participants indicated that a higher adherence to MD was associated with 23 % reduced risk of developing type 2 diabetes (11). In patients with newly diagnosed type 2 diabetes, consumption of MD resulted in a greater reduction of HbA1c levels, higher rate of diabetes remission, and delayed need for diabetes medication, compared to a less specifi c low-fat diet (12). MD enriched with extra-virgin olive oil but without energy restrictions reduced diabetes risk among persons with a high cardiovascular risk (13).…”
Section: And Type 2 Diabetesmentioning
confidence: 99%
“…An extensive metaanalysis including 136,846 participants indicated that a higher adherence to MD was associated with 23 % reduced risk of developing type 2 diabetes (11). In patients with newly diagnosed type 2 diabetes, consumption of MD resulted in a greater reduction of HbA1c levels, higher rate of diabetes remission, and delayed need for diabetes medication, compared to a less specifi c low-fat diet (12). MD enriched with extra-virgin olive oil but without energy restrictions reduced diabetes risk among persons with a high cardiovascular risk (13).…”
Section: And Type 2 Diabetesmentioning
confidence: 99%
“…In addition, randomized controlled intervention studies have revealed that it is effective in the primary prevention of cardiovascular diseases [45], in improving diabetes [46] and cognitive function [47], and recently also in the primary prevention of invasive breast cancer [48]. …”
Section: Discussionmentioning
confidence: 99%
“…Esposito et al performed a two-armed randomized controlled trial to assess the impact of dietary intervention, such as Mediterranean-style diets (Med diets), on the need for anti-hyperglycemic drug therapy and remission of T2DM in those newly diagnosed [9]. The study included 215 men and women who were middle-aged (mean age 52.2 years) and overweight (mean BMI 29.6 kg/m 2 ), were newly diagnosed with T2DM and had never received anti-hyperglycemic medications.…”
Section: Literature Reviewmentioning
confidence: 99%